International consensus on quality indicators for comprehensive assessment of dementia in young adults using a modified e‐Delphi approach. (13th July 2020) - O'Malley, Mary; Parkes, Jacqueline; Stamou, Vasileios; LaFontaine, Jenny; Oyebode, Jan; Carter, Janet
Abstract : Objective: To develop guidance for clinicians about essential elements that can support clinical decision‐making in the diagnostic workup of young onset dementia. Methods/design: Three iterations of a modified e‐Delphi consensus survey comprising 23 international expert clinicians specialising in diagnosis of young onset dementia. Outcome measures: A priori consensus was pre‐defined as 80% of experts ranking statements in the upper threshold on a seven‐point Likert scale that ranged from "not important at all" to "absolutely essential" to diagnosis. Results: 80% consensus was reached on 48 statements that were rated as "absolutely essential" or "very important" to a comprehensive assessment of dementia in a younger adult. In order to inform a subsequent audit of clinical records in which compliance with these statements was assessed, the statements were divided into a Minimum Standard, (consisting of the 15 statements voted by all experts as being "absolutely essential" or "very important") and a Gold Standard where 48 statements were voted by 80% of the experts as being "absolutely essential" or "very important". The experts' response rate across the three rounds was 91.3%. Conclusion: A Minimum Standard and Gold Standard have been created for the diagnostic workup of young onset dementia. The standards provide a clinically useful tool for decision‐making, particularly for generalists and those with less experience in the field. The standards will be used to inform a UK case note audit of recently diagnosed patients with young onset dementia.